2004
DOI: 10.1142/s0218271804006498
|View full text |Cite
|
Sign up to set email alerts
|

A Secret Tunnel Through the Horizon

Abstract: Hawking radiation is often intuitively visualized as particles that have tunneled across the horizon. Yet, at first sight, it is not apparent where the barrier is.Here I show that the barrier depends on the tunneling particle itself. The key is to implement energy conservation, so that the black hole contracts during the process of radiation. A direct consequence is that the radiation spectrum cannot be strictly thermal. The correction to the thermal spectrum is of precisely the form that one would expect from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
333
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(353 citation statements)
references
References 5 publications
17
333
2
1
Order By: Relevance
“…They treat Hawking radiation as a tunnelling process, and the WKB method is used [2,3]. In this way a corrected spectrum, which is accurate to a first approximation, is given.…”
Section: Introductionmentioning
confidence: 99%
“…They treat Hawking radiation as a tunnelling process, and the WKB method is used [2,3]. In this way a corrected spectrum, which is accurate to a first approximation, is given.…”
Section: Introductionmentioning
confidence: 99%
“…When no back reaction effects nor quantum 3 A similar logarithmic correction to the entropy-area law has also emerged from the calculation of one-loop effects of the (quantum) matter fields near the black hole [16]. 4 We now switch from k = = c = G = 1 units of the previous sections to k = = c = 1 to keep track of the Planck-scale suppressed terms. 5 In [17], for example, it is shown that the emergence of such a logarithmic correction can be related to Planck-scale modifications of a particle's quantum localization limit.…”
Section: A Tunnel Through the Quantum Horizonmentioning
confidence: 95%
“…Parikh and Wilczek [3] (see also [4,5]) showed how such a description of black hole radiance is possible if one considers the emission as a transition between states with the same energy. In this way the lowering of the mass of the black hole during the process and the related change in the radius set the barrier through which the particle tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Now it is believed that Hawking radiation arises from the production of virtual particle pairs spontaneously near the inner of horizon due to the vacuum fluctuation. When the negative energy virtual particle tunnels inwards, the positive energy virtual particle materializes as a real particle and escapes to infinity [10][11][12][13][14][15][16][17][18][19][20][21]. But, how does the positive energy particle run?…”
Section: Introductionmentioning
confidence: 99%